Hermann Kurz und die 'Poesie der Wirklichkeit'. Studien zum Frühwerk, Texte aus dem Nachlass - Slunitschek, Matthias (Untersuchungen zur deutschen Literaturgeschichte, 2017)
Hermann Kurz (1813-1873) was among the founders of German historical, realistic, and social narrative in the period before the March Revolution of 1848. The study uses innovative textual interpretation to evaluate the whole continuum of his early works through all genres. It reveals Kurz' use of a poetics derived from both contemporary literature (Schiller, Uhland, Schwab, and Mörike) and earlier works (Gottfried von Straßburg, Grimmelshausen).